Observational evidence of particle hygroscopic growth in the upper troposphere–lower stratosphere (UTLS) over the Tibetan Plateau - Q. He; Q. He; J. Ma; X. Zheng; X. Yan; H. Vömel; F. G. Wienhold; W. Gao; W. Gao; D. Liu; D. Liu; G. Shi; et al. (Atmospheric Chemistry and Physics, 2019)
We measured the vertical profiles of backscatter ratio (BSR) using the balloon-borne, lightweight Compact Optical Backscatter AerosoL Detector (COBALD) instruments above Linzhi, located in the southeastern Tibetan Plateau, in the summer of 2014. An enhanced aerosol layer in the upper troposphere–lower stratosphere (UTLS), with BSR (455 nm) > 1.1 and BSR (940 nm) > 1.4, was observed. The color index (CI) of the enhanced aerosol layer, defined as the ratio of aerosol backscatter ratios (ABSRs) at wavelengths of 940 and 455 nm, varied from 4 to 8, indicating the prevalence of fine particles with a mode radius of less than 0.1 µm. We find that unlike the very small particles (mode radius smaller than 0.04 µm) at low relative humidity (RHi < 40 %), the relatively large particles in the aerosol layer were generally very hydrophilic as their size increased dramatically with relative humidity. This result indicates that water vapor can play a very important role in increasing the size of fine particles in the UTLS over the Tibetan Plateau. Our observations provide observation-based evidence supporting the idea that aerosol particle hygroscopic growth is an important factor influencing the radiative properties of the Asian Tropopause Aerosol Layer (ATAL) during the Asian summer monsoon.